Entrepreneurship Education for Teens: Fostering an Entrepreneurial Spirit Among Students at Angkatan Belia Islam, Penang, Malaysia - Rayyani, Wa Ode; Syahadat, Edy Fitriawan; Sujana, I Wayan; Dhewi, Ratna Marta; Muchriana Muchran; Nabila Hidayani; Laras Lestari; Edi Prayogo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Entrepreneurship education is an important element in equipping young people with the necessary skills and mindset to face future economic challenges. The spirit of entrepreneurship among teenagers through interactive and fun educational activities. This activity was conducted at Angkatan Belia Islam (ABI), Penang, Malaysia, in October 2024, and was designed in the form of inspiring motivational talks and educational games that stimulate critical thinking and creativity. The results of the activity showed that such an interactive approach is effective in improving adolescents' understanding of the basic principles of entrepreneurship as well as motivating them to develop their entrepreneurial potential early on. The results of this activity confirm that entrepreneurship education is not only relevant, but also essential in building an independent, creative and innovative generation in the future.